ANALISIS PENGARUH LINGKUNGAN BISNIS, PERENCANAAN STRATEGIS DAN ORIENTASI KEWIRAUSAHAAN PADA KINERJA BISNIS DENGAN INOVASI SEBAGAI VARIABEL PEMEDIASI - Siti Almaidah Siti Almaidah (Riset Manajemen dan Akuntansi, 2021)
Micro small and medium enterprises (MSMEs) in the structure of the Indonesian economy occupy the first place in quantity and is a new source in the growth of the domestic economy. During the economic crisis, MSMEs have a high endurance to sustain the Indonesian economy, can even survive the global crisis. Besides that MSMEs also have an important role including as the main driver of job creation, and economic growth both nationally and regionally. To deal with the rapidly changing business environment, MSMEs must have a competitive advantage, good strategic planning, entrepreneurial orientation, and effective performance achievement through innovation efforts. This study aims to test and analyze the influence of the business environment, strategic planning and entrepreneurial orientation on business performance with innovation as mediating variables. The sample in this study was 60 MSMEs in the Surakarta region, and sampling uses purposive sampling, with limits according to the criteria set out in the population and willing to be respondents. This study uses a survey research design. The method of analysis is carried out through testing the quality of data and hypothesis testing using path analysis techniques with SPSS tool version 20. The results showed that the business environment, strategic planning, entrepreneurial orientation had a positive and significant effect on innovation. Innovation variables are variables that mediate the influence of the business environment, strategic planning, and entrepreneurial orientation on business performance.